PROFIL JENIS REPRESENTASI SISWA UNTUK MEMECAHKAN PERMASALAHAN DALAM PEMBELAJARAN FISIKA - Richard Semuel Waremra; Merta Simbolon; Syamsul Bahri; Oswaldus Dadi (Universitas Sultan Ageng Tirtayasa, 2021)
This study aimed to determine the profile of the type of representation of students to solve problems in learning physics. This type of research is descriptive quantitative. The sample used in this study was 170 high school and vocational high school students in the Merauke district, and the sampling technique used was purposive sampling. The instrument used in this study was a problem-solving ability test instrument using a multimode representation by the Rosengrant stage and a questionnaire instrument for student responses to various types of representation in physics. The results showed that students could only use a single representation in the form of text, image, and mathematical representations. There are no students who can use the representation of line diagrams, bar charts, and free-body diagrams. The students' questionnaire responses showed that students used different representations in understanding the concept, and the type of representation most used was text representation.